Decrypting E ( STLIN ) E ( DWARD ) cummings poetry : unveiling the unsaid - Moulai hacene, YACINE (University of Mostaganem, 2015)
The dissertation is concerned with making the unfamiliar familiar to the readers of literature, specifically to those who are interested in poetry in general and in e. e. cummings’ (1894 – 1962) poetry in particular. It aims to investigate the extent to which the conventions of poetry are “violated” via the deviation of the normal usage of syntax, phonology, graphology, morphology, and semantics. Furthermore, it foregrounds the importance of literary stylistics as an objective method of analysis leading more or less to an interpretation of literary text that is far from being based on impressions and feelings. Thus, basics of cryptography are explained and the notions of style and stylistics are dwelt upon so that to give a clear idea/ cut between style as a rhetorical notion and stylistics as a linguistic tool. The notion of concrete poetry is also passed under review. All these methodological steps are taken along with a focus on e. e. Cummings’ way of writing/ disfiguring norms of language, where parts of sentences are understood partly in terms of themselves but partly also in terms of their relationship with other expressions in the poem. Many concrete examples that provide supportive proofs to the theoretical parts of the work are presented by implementing/ fusing two disciplines, namely “Cryptology” and “Stylistics” to reach an interpretation of what once was unreadable and uneasy to access to